Desain Modul Matematika Siswa Berbasis PMRI Kelas IV Sekolah Dasar - Heru Heru; Refi Elfira Yuliani; Mazro'atul Khoeriyah; Rieno Septra Nery (Program Studi Pendidikan Matematika UIN Raden Fatah Palembang, 2020)
This study aims to develop a student mathematics module based on the Indonesian Realistic Mathematics Education (PMRI) approach to the material of factors and multiples of a number in grade IV Elementary School to help with these difficulties. The research method used in this research is development research using the Four-D Models (4-D) development model, which consists of four stages: define, design, develop, and disseminate. The research subjects were fourth-grade elementary school students. From this research, it was found that; 1) the developed module was declared valid by material, media and language experts; 2) the mathematics module that was developed practically through limited trial activities with the results of the percentage of the remaining assessment questionnaires distributed was 94.32%; 3) the developed module has a potential effect on student learning outcomes, which can be seen from the final average score of students, which is 85.33, which means that student learning outcomes are categorized as very good. Based on the study results, it can be stated that the developed module is valid, practical and has a potential effect on improving learning outcomes.